The Impacts of Communication in Transformational Leadership and ICT on Customer Satisfaction in the Educational Sector - Elfindah Princes; Tita Rosita; Rais Hidayat (Universitas Tarakanita, 2022)
This research aims to assess the impacts of implementing Transformational Leadership (TL) and Information Communication and Technology (ICT) in the education sector to increase Customer Satisfaction especially during uncertainties. Using the quantitative approach, this research argues the importance of customer satisfaction in education business influenced by the communication skills implemented in Transformational Leadership and ICT. Data from 286 respondents using stratified data sampling are gathered and analysed using PLS. The results showed that TL has a stronger influence than ICT in improving customer satisfaction with a value of 0.547 and 0.329, respectively. This study indicates the importance of Communication to build relationships with customers in Transformational Leadership to improve Customer Satisfaction in education. With transformational Leadership and the application of ICT, educational institutions as business units can provide better service and, as an implication, can improve company’s profit